Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Expertgruppen för biståndsanalys (EBA), 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.